Longitudinal evaluation of olfactory function in individuals with Gaucher disease and GBA1 mutation carriers with and without Parkinson's disease - Lopez, Grisel J.; Lichtenberg, Jens; Tayebi, Nahid; Ryan, Emory; Lecker, Abigail L.; Sidransky, Ellen (Frontiers in Neurology, 2022)
Objective: Biallelic mutations in GBA1, encoding the enzyme glucocerebrosidase, cause the lysosomal storage disorder Gaucher disease (GD). Mutations in GBA1 are also the most common genetic risk factor for Parkinson disease (PD). However, most mutation carriers never develop parkinsonism. Olfactory dysfunction is often a prodromal symptom in PD, appearing many years prior to motor dysfunction. We assessed olfactory function longitudinally in individuals with and without parkinsonism carrying at least one GBA1 mutation. Methods: 117 individuals in a natural history study of GD at the National Institutes of Health were evaluated using the University of Pennsylvania Smell Identification Test (UPSIT) during a 16-year period. Seventy patients with GD (13 with PD) and 47 GBA1 carriers (9 with PD) were included. Fifty-six of the total (47.9%) had multiple visits, and UPSIT screening was performed two to six times, with intervals between testing ranging from 2-6 years. Comparative data from 340 patientswith idiopathic PD and 179 healthy controls were obtained from the Parkinson’s Progression Markers Initiative (PPMI) database. Statistical analysis was performed using R. Results: GBA1 heterozygotes and homozygotes with PD exhibited evere hyposmia and anosmia. 84% of those without parkinsonism had UPSIT scores over 30, which were maintained over time. No statistically significant difference in UPSIT scores was found between mutation carriers with and without a family history of parkinsonism. A small group of individuals without PD scored in the moderate-severe microsmia range. No significant differences in olfaction were found among our GBA1-PD cohort and the PPMI idiopathic PD cohort.